Theoretical and experimental studies on large deflection analysis of double corrugated cantilever structures. (1st October 2021) - Kumar, Deepak; Ali, Shaikh Faruque; Arockiarajan, A.
Abstract: Corrugated structures are made up of panels with periodic profiles. These are used as a compliant mechanism and as core in sandwich plates for their direction dependent stiffness. Modeling and large deflection analysis of corrugated structure play an essential role in their design and application. This work proposes an iterative scheme for the large deflection analysis of double corrugated cantilever structures subjected to end point loads and uniformly varying load using a chain algorithm. The double corrugated structure is modeled by discretizing it into several basic corrugated units. Each basic unit is then split into two halves, and a solution is arrived by using an error minimization. The deflection of each of the halves is obtained, discretizing it into beam elements. Finally, the deflection of the double corrugated structure is calculated by assembling the deflection of each of the basic corrugated units. Furthermore, prototypes of the double corrugated structure are fabricated using aluminum sheets, and a moment actuation test is performed. The deflections of these prototypes obtained using the proposed iterative scheme are compared with ABAQUS and validated with experiments, and the results are found to be in good agreement. An example problem is also solved, demonstrating the practical application of the proposed iterative scheme in the design of a double corrugated variable camber morphing wing with aerodynamic load actuated by the tendon-pulley system.